AKTIVITAS AMILASE BAKTERI YANG DIISOLASI DARI SUMBER AIR PANAS CISEENG BOGOR - Amri, Erismar; Widhyastuti, Nunuk; Artika, I Made (IAIN Batusangkar, 2010)
This research was aimed at studying the activities of amylase produced by isolate bacteria which were isolated from hot water resource, Ciseeng Bogor. Four among the nine isolate bacteria grown on NA media showed the activities of amylase. The character of Amylase was analyzed in 2 isolates, A1 and A3. Isolate A1 was optimally active at pH 3, 55 C, meanwhile isolate A3 was optimally active at pH 4, 50 C. The amylase resulted from either isolate A1 or isolate A3 was acid amylase. Both of the isolates were relatively stable at pH acid, whereas the amylase resulted from A3 was not stable on pemanasan in 30 minutes, and the amylase from A1 increased after being incubated at more than 60 C in 30 minutes. In conclusion, isolate A1 identified as Bacillus Coagulans indicated the optimal activities when it was grown at pH 6 and at the 14th hour of incubation.Key words: amylase, isolation, enzyme